Video Quality Assessment of Early SKIP/DIS for 3D-HEVC Complexity Reduction - Bubolz, Thiago; Conceição, Ruhan; Almeida, Heitor; Moreira, Érick; Zatt, Bruno; Tavares, Tatiana; Porto, Marcelo; Corrêa, Guilherme (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
This paper presents a quality analysis of 3D videos encoded with the 3D extension of the High Efficiency Video Coding (HEVC) standard, 3D-HEVC, using the Early Skip/DIS heuristic to reduce complexity. In addition to comparing the heuristic from a quality point of view, the analyses were performed with objective and subjective methodologies with the goal of comparing the reliability of the metrics. Three metrics were employed in the objective evaluation: Peak Signal-to-Noise Ratio (PSNR), Structural Similarity (SSIM) e Most Apparent Distortion (MAD). The subjective analyses considered the Mean Opinion Score (MOS) metric using double stimulus. The evaluation results demonstrated that the Early Skip/DIS solution has no significant impact in image quality in comparison with videos encoded with the unmodified 3D-HEVC reference encoder.